VALIDATION OF THE DRIVER BEHAVIOUR QUESTIONNAIRE OF DRIVERS IN BULGARIA (TRAKIA JOURNAL OF SCIENCES, 2025)
The Driver Behaviour Questionnaire (DBQ) is a widely used measure of driving behaviours that may increase a driver's risk of involvement in a crash. Purpose: The current research aimed to evaluate the validity of a 46-item questionnaire among Bulgarian drivers using confirmatory factor analysis. Method: Data on various attitudes towards road safety were gathered through an online survey. One hundred and sixty responses were obtained from licensed motor vehicle drivers, comprising 73.125% males and 26.875% females, aged between 18 and 61, with driving experience ranging from 1 to 5 years. Principal component factor analysis (with Varimax rotation) and confirmatory factor analysis (CFA with maximum likelihood estimation) were conducted to examine the underlying dimensions and model fit.Results indicated that the seven-factor structure includes “lack of skills”, “driver perception”, “road aggression”, “distracted driving", “neglected attitude”, “arrogance” and “neatness”. Confirmatory factor analysis supported the 46-item scale within the Bulgarian sample. Discussion: The models fit relatively well; all seven-factor structures effectively explain the data. The next step will be to identify which driver subgroups should be targeted in interventions and to determine the most suitable form of intervention to implement.